Impact of mTOR expression on clinical outcome in paediatric patients with B-cell acute lymphoblastic leukaemia – preliminary report - Ulińska, Edyta; Mycko, Katarzyna; Sałacińska-Łoś, Elżbieta; Pastorczak, Agata; Siwicka, Alicja; Młynarski, Wojciech; Matysiak, Michał (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : To characterise expression of mTOR (mammalian target of rapamycin) in childhood B-cell acute lymphoblastic leukaemia (ALL), and to evaluate a possible link between mTOR and clinical characteristics. Material and methods : The examined group consisted of 21 consecutive patients, aged 1–18 years, diagnosed with B-cell ALL in 2010, and 10 relapsed B-cell ALL patients diagnosed for the first time between 2009 and 2011, who developed relapse before 2014. All subjects were treated in the Department of Paediatric Haematology and Oncology of the Medical University of Warsaw according to the ALL-IC BFM 2002 Protocol. We evaluated mTOR and phospho-mTOR expression by immunohistochemistry using rabbit monoclonal antibodies. Results : mTOR expression was found to be significantly associated with the risk of relapse and was more frequent in ALL recurrence. No significant relationship was detected between mTOR expression and other features of high-risk disease in paediatric ALL. Conclusions : mTOR activity could be considered a high-risk feature in paediatric B-cell ALL. Expression of mTOR kinase is observed remarkably more frequently in disease recurrence than at first diagnosis, indicating higher proliferative and survival potential of leukaemic cells in relapse. Routine analysis of mTOR activity could be performed to select patients that may potentially benefit from mTOR inhibitors (MTI) treatment.